Formula For the Sum Of the First N SquaresDate: 02/20/98 at 10:35:55 From: Andres Sandin Subject: Formula for the sum of the first N squares Can you show me how (1^2 + 2^2 + 3^2 + ... + N^2) becomes (N * (N + 1) * (2N + 1)) / 6 Thanks. Date: 02/20/98 at 11:55:45 From: Doctor Sam Subject: Re: Formula for the sum of the first N squares Andres, This is a lot easier to do with pictures, but I'll try to show you an algebra approach to this formula. It makes use of this cubing pattern: (x + 1)^3 = x^3 + 3x^2 + 3x + 1 That is, to cube one more than a number x, first cube x, then triple x^2, then triple x, and then add these to 1. Okay? 1^3 = (0 + 1)^3 = 0^3 + 3 ( 0^2 ) + 3 (0) + 1 2^3 = (1 + 1)^3 = 1^3 + 3 ( 1^2 ) + 3 (1) + 1 3^3 = (2 + 1)^3 = 2^3 + 3 ( 2^2 ) + 3 (2) + 1 4^3 = (3 + 1)^3 = 3^3 + 3 ( 3^2 ) + 3 (3) + 1 etc. n^3 = (n-1 + 1)^3 = (n-1)^3 + 3 (n-1)^2 + 3 (n-1) + 1 (n+1)^3 = (n + 1)^3 = n^3 + 3 n^2 + 3 n + 1 ---------------------------------------------------------------------- now add all these up in columns. The left side is the sum of the cubes from 1 to n+1: 1^3 + 2^3 + 3^3 + ... + n^3 + (n+1)^3 The first column on the right is also the sum of cubes but starting at 0 and ending at n: 0^3 + 1^3 + 2^3 + ... + (n-1)^3 + n^3 The next column on the right has 3 times the sum of the squares from 0^2 to n^2 The next column has 3 times the sum of the integers from 0 to n. The last column has n+1 ones. [not n ones...n+1 ones!] 1. All of the cubes cancel except for (n+1)^3 2. The sum of the squares is what we are looking for ... call this S 3. The sum of the integers 1+2+3+...+n = n(n+1)/2 4. The sum of n+1 ones is just n+1. Now combine these: (n+1)^3 = 3S + 3[ n(n+1)/2 ] + n + 1 Bring everything together: n^3 + 3n^2 + 3n + 1 - 3n^2/2 - 3n/2 - n - 1 = 3S Simplify: n^3 + 3n^2/2 + n/2 = 3S Multiply through by 2 to clear fractions: 2n^3 + 3n^2 + n = 6S Factor: n ( 2n^2 + 3n + 1) = 6S Factor again: n ( 2n+1) (n+1) = 6S Rearrange and solve for S = 1^2 + 2^2 + ... + n^2: S = n(n+1)(2n+1)/6 ! I hope that helps. -Doctor Sam, The Math Forum Check out our web site http://mathforum.org/dr.math/ Date: 02/20/98 at 12:08:50 From: Doctor Rob Subject: Re: Formula for the sum of the first N squares This can be proved using the Principle of Mathematical Induction. First, lets verify it for N = 1: 1^2 = 1 = 1*(1+1)*(2*1+1)/6. Then if it is true for N, let's show that it must be true for N+1: 1^2 + 2^2 + 3^2 + ... + N^2 = N*(N+1)*(2N+1)/6, (1^2 + 2^2 + 3^2 + ... + N^2) + (N+1)^2 = N*(N+1)*(2N+1)/6 + (N+1)^2, 1^2 + 2^2 + 3^2 + ... + N^2 + (N+1)^2 = (N+1)*[N*(2*N+1)/6 + N + 1], = (N+1)*(2*N^2+N+6*N+6)/6, = (N+1)*(2*N^2+7*N+6)/6, = (N+1)*(N+2)*(2*N+3)/6, = (N+1)*[(N+1)+1]*[2*(N+1)+1]/6, which is the statement we wanted to prove for N+1. Now apply the Principle of Mathematical Induction to conclude that the statement is true for all N >= 1. Another way to see this is as follows. Let f(N) = N*(N+1)*(2N+1)/6. Then f(N) - f(N-1) = N*(N+1)*(2N+1)/6 - (N-1)*[(N-1)+1]*[2*(N-1)+1]/6, = N*(N+1)*(2N+1)/6 - (N-1)*N*(2*N-1)/6, = N*[(2*N^2+3*N+1)-(2*N^2-3*N+1)]/6, = N*(6*N)/6, = N^2. Now 1^2 = f(1) - f(0), 2^2 = f(2) - f(1), 3^2 = f(3) - f(2), ... ... (N-1)^2 = f(N-1) - f(N-2), N^2 = f(N) - f(N-1). Add all these up, and see that on the right side, there is massive cancellation. The result is 1^2 + 2^2 + 3^2 + ... + N^2 = f(N) - f(0) = N*(N+1)*(2N+1)/6. If this kind of cancellation occurs in a sum, it is called a "telescoping sum." This can be a very useful trick to know in some contexts. The problem is to find the function f(N) for which f(N) - f(N-1) is a given function of N. In this case, it is given to you. In other situations, it may not be. But that's a different story! -Doctor Rob, The Math Forum Check out our web site http://mathforum.org/dr.math/ |
Search the Dr. Math Library: |
[Privacy Policy] [Terms of Use]
Ask Dr. Math^{TM}
© 1994- The Math Forum at NCTM. All rights reserved.
http://mathforum.org/dr.math/